An insight on the physical mechanisms responsible of power augmentation in a pair of counter-rotating Darrieus turbines. (15th May 2023) - Mohamed, Omar S.; Melani, Pier Francesco; Balduzzi, Francesco; Ferrara, Giovanni; Bianchini, Alessandro
Graphical abstract: Highlights: Detailed analysis on the power augmentation mechanisms in twin counter rotating Darrieus turbines. Rotor interactions suppress inflow expansion, increase angle of attack, and generate higher lift. Effects are quantified via AoA calculation through flow sampling. The power augmentation mechanism is more pronounced at higher tip speed ratios. Physical insight key to improve multiple Darrieus turbines and tuning low-fidelity methods. Abstract: In recent years, Darrieus turbines have received increasing attention by both the industrial and the academic sector due to their advantages for both wind and hydrokinetic applications. Experimental and numerical investigations showed that the interaction between closely spaced Darrieus rotors can lead to a significant increase in their efficiency. To date, however, the physics underlying this phenomenon has been only argued or qualitatively discussed, since no robust method to determine the actual angle of attack was available. This study provides a novel insight into the physical mechanisms that lead to performance enhancement in twin Darrieus rotors. A pair of counter-rotating, two-blade Darrieus hydrokinetic turbines are investigated while spinning in both the revolution senses, namely, inward and outward, by means of unsteady Computational Fluid Dynamics. After a preliminary analysis on the effect of rotor spacing, an improved flow sampling method is used to analyze the instantaneous flow kinematics past the blades in combination with computed blade loads, thus allowing the calculation of lift and drag forces. Results show that the optimum center-to-center distance for the turbines under consideration is 2D. Also, it is shown that the optimum operating point of the twin rotors tends to shift toward higher Tip-Speed Ratios (TSRs). Compared to the stand-alone turbine, the efficiency improves by 16.1% and 8.7% for the inward and outward twin rotors setups, respectively. A detailed study of the local flow field shows a complete suppression of the streamtube expansion within the area of mutual interactions between the adjacent rotors. This allows more momentum flux to enter the rotor area compared to that of the isolated rotor. More interestingly, it is observed that the change in the inflow velocity direction leads to an increase in the angle of attack for both the inward and outward setups, causing an increase in the generated lift, which is found as the main reason for the efficiency improvement.